Left Ventricular Diastolic Function in Patients on Hemodialysis. (1st August 2010) - Raizada, Veena; Skipper, Betty; Taylor, Robert A.; Luo, Wentao; Harford, Antonia A.; Zager, Philip G.; Rohrscheib, Mark; Spalding, Charles T.
Abstract : Background: Previous studies have shown that the assessment of Doppler mitral flow velocity (DMFV) curves can be used to predict prognosis owing to left ventricular (LV) diastolic dysfunction in certain specific diseases. Our aim was to study whether the prognostic value of DMFV curves is affected by the many end-stage renal disease factors, such as chronic uremia and long-term hemodialysis (HD), which cause LV diastolic dysfunction and death. Methods: Retrospective echo Doppler studies obtained 10 to 12 hours after HD in 90 patients (52 males; mean age, 56 years) were analyzed to determine changes in deceleration time (DT) of the early mitral filling wave ( E ) and the ratio of E to the atrial velocity ( A ). The study findings (n = 83) showed 2 groups of DT: long DT (DT > 240 milliseconds) and normal/short DT (DT ≤ 240 milliseconds). Continuous variables of LV size using internal dimensions, systolic function using ejection fraction, hypertrophy using wall thickness and mass, and pulmonary hypertension and E / A were compared between the 2 groups. Results: Patients with long DT versus normal/short DT had lower absolute and indexed LV mass ( P = 0.03 and P = 0.02, respectively) and pulmonary hypertension ( P ≤ 0.001), without a significant difference in LV systolic function or E / A . The mortality rate, adjusted for age and sex, was lower with long DT versus normal/short DT, with a hazard ratio of death, 0.44 (95% confidence interval, 0.23-0.86, P = 0.02). Conclusions: Our study identified characteristics of DMFV curves in patients on long-term HD, which are clearly of value in predicting outcomes and survival in these patients.